Building Resilience through Counseling in The New Normal - Nurul Hidayati (Proceedings Series on Social Sciences & Humanities, 2021)
This study focused on the dynamic process a 26 years old woman is going through in building her resiliency. The woman used to be verbally and emotionally abused by her stepmother, and that experience brings a significant impact on her life. This article’s primary purpose is to describe how the woman’s dynamic faces the problems and how she uses the counseling process, e-counseling, and face-to-face support to transform herself into a resilient and forgiving person. It also takes into account the woman’s risk factors and protective factors. This is a case study, and the data was collected from a single case using in-depth interviews, observation, and psychological assessment. The data analysis is using thematic analysis. The result showed that the counseling process has helped the woman grow, raising her ability to cope with her problems, helped her to become more resilient, and become more forgiving and release some of her burdens.